Posttreatment Non-Improved Vocal Cord Mobility Indicates the Need of Salvage Surgery for Hypopharyngeal Carcinomas - He, Yu-qin; Zhang, Xi-wei; Zhu, Yi-ming; Ni, Xiao-guang; Huang, Ze-hao; An, Chang-ming; Yi, Jun-lin; Liu, Shao-yan (Frontiers in Oncology, 2021)
Introduction: We aimed to analyze the relationship between the changed status of vocal cord mobility and survival outcomes. Methods: Seventy-eight patients with dysfunctional vocal cords and hypopharyngeal carcinomas accepted nonsurgical treatment as the initial therapy between May 2009 and December 2016. Vocal cord mobility was assessed before and after the initial nonsurgical treatment. The cord mobility status was classified as normal, impaired, and fixed. Patients with improved mobility (IM) (n =56) were retrospectively analyzed for disease-free survival (DFS), recurrence-free survival (RFS), and overall survival (OS) and compared with 22 patients with nonimproved mobility (non-IM). Results: Fifty-six (71.8%) patients had improved cord mobility after the initial nonsurgical treatment. The nonimproved cord mobility was significantly associated with shortened DFS (P=0.005), RFS (P=0.002), and OS (P<0.001). If nonimproved cord mobility was regarded as an indicator for local-regional recurrence within 1 year, the sensitivity and the specificity were 60.9%, 87.5% respectively. The multivariate analysis showed that improved cord mobility (P=0.006) and salvage surgery (P=0.015) were both independent protective factors for OS. Conclusion: Changes in cord mobility are a key marker for predicting prognosis. Nonimproved cord mobility may indicate a high possibility of a residual tumor, therefore, patients whose cord mobility remains dysfunctional or worsens after nonsurgical treatment might need an aggressive salvage strategy.